DEVELOPMENT OF AN IMPROVED SAW GIN WITH A WORKING ELEMENT (Scientific journal of the Fergana State University, 2025)
In this work, the design of traditional saw gins has been improved, with modernization of the working parts—saw discs, brush drums, and seed separation mechanisms. The improved model takes into account the optimal shape and arrangement of the saws, reduces fiber damage, increases energy efficiency, and introduces a waste reduction mechanism.